Variation in Arterial CO2 is a Stronger Determinant of Brain Tissue Oxygenation Than its Synchronous Value in Critically Ill Patients With Acute Brain Injury - Joanie Martineau, MD, MSc; Francis Bernard, MD; Alexandrine Gagnon, MD; Virginie Williams, PhD; Sabrina Araujo de Franca, BSN; David Williamson, BPharm, PhD; Yiorgos Alexandros Cavayas, MD, Msc (Critical Care Explorations)
OBJECTIVES:. In critically ill patients with acute brain injury (ABI), maintaining intracranial pressure (ICP) and brain tissue oxygenation (PbtO2) within targets could prevent secondary neurologic injury. Tight control of CO2 (Paco2), a potent regulator of cerebrovascular tone, is generally advocated, but its vasomotor effect may be short-lived. Our aim was to compare the effect of the synchronous Paco2 vs. its variation from a previous baseline on PbtO2 and ICP. DESIGN:. We performed a post hoc analysis of a prospective cohort study collecting arterial blood gas (ABG) values alongside synchronous neuromonitoring variables. Linear mixed-effects models were fitted to evaluate the association between Paco2 and/or Paco2 variation from its average of the last 8–24 hr vs. PbtO2 and ICP, while controlling for cerebral perfusion pressure and Pao2. SETTING:. Mixed medical-surgical ICU of Sacré-Coeur Hospital, an academic trauma center in Montreal, Canada. PATIENTS:. All consecutive adult patients admitted for ABI with ICP and PbtO2 monitoring between May 2017 and November 2021. INTERVENTIONS:. None. MEASUREMENTS AND MAIN RESULTS:. We included 78 patients with 3047 ABG-neuromonitoring couplets. The model using the variation of Paco2 from its average of the last 24 hr displayed the best performance for the prediction of PbtO2 (coefficient 0.37; 95% CI 0.21–0.53). The strongest predictor of ICP was the variation of Paco2 from its average of the last 8 hr (coefficient 0.17; 95% CI 0.10–0.23). CONCLUSIONS:. Variation in Paco2 from baseline is a more significant determinant of PbtO2 and ICP than the absolute Paco2 value at a given time. There may be a baseline vasomotor reset when patients are exposed to a given level of CO2 for 8 to 24 hr. Therefore, sustained intentional manipulation of Paco2 is unlikely to have lasting effects and slower correction rates of high or low Paco2 could help prevent brain tissue hypoxia or intracranial hypertension, respectively.